Management of the ‘Take a Nap’ Program as a Strategy to Improve Students’ Learning Concentration in Fullday School : Manajemen Program “Take a Nap” Sebagai Strategi meningkatkan Konsentrasi Belajar Siswa Fullday School - Adzani, Muhammad Ridho; Nurdyansyah (Indonesian Journal of Innovation Studies, 2026)
General Background: Fullday school extends learning hours and may contribute to student fatigue, drowsiness, and reduced concentration during afternoon lessons. Specific Background: SD Muhammadiyah 4 Zamzam, Sidoarjo, implements a structured nap-time program for first- to third-grade students to address these conditions. Knowledge Gap: Previous studies have discussed daytime napping and learning-related outcomes, but contextual implementation as an educational management innovation remains limited. Aims: This study analyzes the implementation of the nap-time program and its role in supporting students’ learning concentration. Results: Using a descriptive qualitative approach, data were collected through observation, semi-structured interviews, and documentation involving teachers and students. The program was associated with greater student focus, participation, alertness, and learning readiness, while challenges included limited facilities, difficulties falling asleep, and uneven parental understanding. Novelty: The study integrates nap-time management with behavioral change in a fullday school context. Implications: Sustainable implementation requires facility improvement, duration adjustment, and continued parental engagement. Key Findings Highlights Reduced afternoon drowsiness and improved student alertness were reported. Teachers observed stronger participation following scheduled rest periods. Implementation challenges involved facilities, sleep adaptation, and parental understanding. Keywords : Nap-Time Program, Learning Concentration, Full-Day School, Educational Management, Behavioral Change